Rapid isolation and recovery of Salmonella using hollow glass microspheres coated with multilayered nanofilms - Rutwik Joshi; Hesaneh Ahmadi; Md Nayeem Hasan Kashem; Fariha Afnan; Siva Parameswaran; Chau-Chyun Chen; Gizem Levent; Wei Li (Materials Today Bio)
Timely isolation, recovery, and identification of Salmonella from food samples is essential for prevention and control of foodborne Salmonella outbreaks. Traditional culture-based Salmonella isolation and serotyping techniques are time consuming and labor intensive. Despite the progress of innovative microfluidic or immunomagnetic isolation techniques, sophisticated lab equipment and microfabrication are often needed. Here, we present a novel, rapid yet simple method for isolation and recovery of Salmonella from mixed bacterial populations in food matrices and blood. This method utilizes self-floating hollow glass microspheres (HGMS) coated with biodegradable layer-by-layer (LbL) films and Salmonella specific antibodies. The isolation and recovery process can be completed in less than 2 h, without any sophisticated laboratory equipment or external force. In this study, we demonstrate that Salmonella can be captured due to antigen-antibody interactions on the surface of HGMS, allowing them to float to the top. The HGMS can then be washed and subjected to enzymatic degradation of the LbL film to recover the captured bacteria. The recovered Salmonella can subsequently be grown on selective agar plates for further analysis. Recovery efficiency of up to 22 % and detection limit of 100 CFU/mL were achieved. This method is expected to provide a viable alternative to traditional isolation techniques, especially in resource limited areas.